Distribution of occlusal contacts in asymptomatic young adults - Wieczorek, Aneta; Loster, Jolanta; Loster, Bartlomiej; Sierpinska, Teresa; Golebiewska, Maria (Journal of Stomatology, 2015)
The proprioceptive receptors in teeth give position signals and have direct influence on the design of the functional pattern. Functional occlusal harmony means the occlusal relationship of opposing teeth in all functional ranges and movements, providing the greatest masticatory efficiency without causing undue strain or trauma to the supporting tissues. Aim of the study. To evaluate whether, for individuals who have completed development and who do not show signs of any functional disorders of the stomatognathic system (as measured by the RDC/TMD), the occlusal contacts are distributed symmetrically along the midline. Material. 18-year-old volunteers comprised students from three randomly selected high schools in Cracow, Poland showing no symptoms of TMD based on an RDC/TMD examination. Method. The examination consisted of an interview regarding the general state of health, a medical examination, and a dental examination. The participants were then given the RDC/TMD questionnaire in its internationally accepted Polish version. All the study participants underwent a T-scan recording using a commercially available T-Scan III evolution 7.01 Results. Analysis of the distribution of occlusal contacts shows that all the occlusal classes were shifted to the left side, and that there were no significant differences between them. Analysis of the distribution of occlusal contacts also showed no significant differences between genders. The distribution of occlusal contacts was shifted to the left side of the midline. Conclusion. The distribution of occlusal contacts in young adults in relation to the midline is not equal, and dominates on the left side.